Centralization of Consumer Financeing at BNI Shariah JABODETABEK Branches Through Business Strategy Analysis of Griya iB Hasanah - Utama, Andenko; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2014)
Abstract - The market share of mortgage financing (KPR) in Indonesia is still very wide open with an estimated population in 2012 was 293.174, in which 85 % of the total population are Moslems. Based on data from Bank Indonesia ( BI ), in the fourth quarter of 2012, 80 % of Indonesian people had been using mortgage as a source of financing for home purchases. Meanwhile, 11.33 % using gradually cash method (cash in advanced), and 8.67% with hard cash method . To seize the market to 80%, management of BNI Syariah has been implementing the  policy in liberalization of sales area and changes in the structure of business unit in its branches of Jabodetabek area. It is aimed to accelerate the growth of Griya iB Hasanah. With the support of the online system (EFO) in processing each application of Griya iB Hasanah, BNI Syariah has the confidence to be able compete in the mortgage industry. In general, the measures taken by BNI Syariah were able to accelerate the growth of the branches in the Jabodetabek area. However, that acceleration was not spead evenly in all branches in the Jabodetabek area. In addition, the time of the application submission process was still uneven and not yet fulfill the SLA of BNI Syariah ie, 3 (three) working days. Up to Q3 of 2013, the growth of  Griya iB Hasanah were dominated by the Branch of BNI Syariah Fatmawati (FMS) and North Jakarta Branch (JKS). In order to find the cause of the problem, it was performed by the comparison of performances between the branches in Jabodetabek area who had a good performance and the low performance through the internal and external environment analysis. The model of Value Chain analysis and Porter's Five Forces was used to determine the root of the problems. Those were encountered as lack of ability, lack of competency, the amount of human resources involved in sales activities, and uneven process of the Griya iB Hasanah product therefore, the sales activity of Griya iB Hasanah was not running effectively and efficiently. The root of the problems encountered are described by using Fishbone Diagram.This final tesis has the improvement proposal in product sales activities of Griya iB Hasanah by improving the sales and process unit, using the business strategy approaches. Accordingly, the  problems are expected, to be resolved.The centralization of consumer financing in the Jabodetabek area is intended to be a solution for the uneven growth expansion of Griya iB Hasanah and irregulerly time of filing the application process of Griya iB Hasanah at BNI Syariah branches in Jabodetabek area. Thus, each unit is expected to have activity more focused, effective, and efficient both in terms of utilization of human resources and the processing.  Keywords: Strategi bisnis, KPR.